Melhora da performance eletroquímica de folhas de grafite: Ativação eletroquímica versus ativação por plasma - Pereira, Jian Felipe da Silva (2019)
Flexible pyrolytic graphite sheets or graphite paper (GP) are a promising source of disposable (low-cost) electrochemical sensors. This work demonstrates the improvement in the electrochemical performance of graphite paper either after a simple electrochemical activation in acid media using cyclic voltammetry or after cold reactive plasma treatment using CO2 and O2 gases. Cyclic voltammetry of the redox probe ferri-ferrocyanide showed higher electrochemical reversibility on the treated surfaces, which was corroborated by the data obtained by electrochemical impedance spectroscopy (lower charge transfer resistance). Scanning electron microscopy revealed a high number of grooves on the treated surfaces after both electrochemical and plasma treatments and Raman spectroscopy showed more structural defects (higher D/G ratios), which may explain the improved cyclic voltammetric response of the redox probe. To evaluate the possible application of these sensors in electroanalysis, the graphite paper was evaluated for dopamine detection using cyclic voltammetry and amperometry under flow conditions. Improved performance on treated surfaces, especially after CO2-plasma treatment, was verified. The electrochemical activation is a simple strategy to improve the sensing properties of graphite paper; however, cold-plasma treated surfaces provided better sensing properties probably due to the production of higher number of structural defects.